IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA - Rahmah, Jihan Aulia; Karyanto, Yunus; Effendi, Prisna Andreanus; Imami, Umi Farih Nur; Baeti, Faedah Nur; Yolanda , Graciella; Ardiyansyah, Julysa Ahmad (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
Currently, the school curriculum still has limitations in terms of flexibility, so it cannot fully adapt to the needs of students. In school and classroom environments, there are various characteristics of students with different interests, talents and learning styles. Student activity in learning is an indicator of the success of the learning process. Based on the results of observations made by researchers through direct observation in class This condition is caused by learning methods that are still conventional, where students receive more material directly without active involvement in the learning process. This situation often results in students feeling less enthusiastic or bored, so they do not pay full attention to the material presented by the teacher. Therefore, this research aims to increase student participation through the implementation of differentiated learning that is adapted to the learning style of each student at the Satya Widya Tourism Vocational School, Surabaya. This classroom action research was carried out in two cycles, with research subjects of 30 students from class XI Culinary 1. The techniques used in this research included observation and documentation, while increasing student activity in each cycle was analyzed based on the research results obtained. The research results show that students started from pre-cycle, cycle I and cycle II, with the average student activity increasing. In cycle I, activeness increased from 74.38% to 83.75%, showing an increase of 9.37%. Furthermore, in cycle II, there was a further increase of 7.5%, reaching 91.25%. Overall, the increase in student activity based on this data reached 16.87% so that, This research has met the indicators of success in increasing active student participation.